PENGARUH PERMAINAN DAN MOTIVASI ANAK TERHADAP PENGUASAAN KONSEP MATEMATIKA ANAK USIA DINI - Pratiwi, Athur Nina (Jurnal CARE (Children Advisory Research and Education), 2013)
This study aimstolook at the influence of games and motivation towards students mathematics achievement. Gamesincludes Ulartanggaand monopoli. Motivationincludes thehigh motivationandlow motivation. The method usedisan experimental method. While thedesign usedis thetreatment used by level of 2x2. Research hypotheses were tested using analysis of variance (ANAVA) two lines. The study concluded that: (1) the group of students mathematics achievementÂ  who were given the monopoli is higher than the group of students mathematics achievementÂ  are given ular tangga, (2)there is the influence of games and motivation towards students mathematics achievement, (3)special groups of children who have high motivation, students mathematics achievement who were given themonopoliis higher thanthegroup of students mathematics achievement are givenular tangga, (4) specialgroups of children who have low motivation, students mathematics achievement who were given themonopoli is lower thanthegroup of students mathematics achievement are given ular tangga.Key words : Games, motivation, students mathematics achievement